Hardening components
Patent Information
- Application Number
- JP2025143674
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2025-08-29
- Publication Date
- 2026-10-14
AI Technical Summary
【0009】 本発明の硬化性組成物によれば、防滑性、仕上り性等に優れた被膜が形成できるとともに、汚染物質等の入り込みを抑制し、被膜の美観性を保持することができる。
Smart Images

Figure 2026167381000001 
Figure 2026167381000002 
Figure 2026167381000003
Abstract
Description
Technical Field
[0001] The present invention relates to a novel curable composition. The composition of the present invention is particularly suitable as a coating material for floor surfaces.
Background Art
[0002] Conventionally, various materials such as urethane-based, epoxy-based, and acrylic-based materials have been used as coating materials for floor surfaces. By using such materials, the floor surface can be protected, and it is also possible to impart a desired color to the floor surface. However, when high-level performance is required in terms of chemical resistance, strength, and the like, it is currently difficult for the aforementioned materials to sufficiently satisfy such requirements.
[0003] Patent Document 1 describes a cement composition for forming floor coatings that contains a polyol of a specific composition, a polyisocyanate, hydraulic cement, and water. According to such a composition, excellent physical properties in terms of chemical resistance, strength, and the like can be ensured.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0005] The compositions described in the above-mentioned patent document are typically stored in at least three components: a first component containing polyol and water, a second component containing a polyisocyanate compound, and a third component containing cement. These components are then mixed together before application to floors and other surfaces. If slip resistance is required, coarse aggregate is further added. However, with compositions like those described in the above-mentioned patent document, adding coarse aggregate can easily create fine voids in the resulting film, potentially impairing the finish. Furthermore, these voids can easily become filled with contaminants, potentially impairing the aesthetic appeal.
[0006] This invention has been made in view of the above-mentioned problems, and aims to provide a curable composition that is excellent in slip resistance and finish, as well as suppressing the penetration of contaminants and other substances, and maintaining the aesthetic appearance of the coating. [Means for solving the problem]
[0007] To solve these problems, the inventors conducted diligent studies and came up with a curable composition comprising a main component (1) containing a polyol compound, a surfactant, and water, a curing agent (2) containing a polyisocyanate compound, and a powder component (3) containing cement, wherein the main component (1) contains a specific polymer, and thus completed the present invention.
[0008] In other words, the present invention has the following features. 1. A curable composition comprising a main component (1) containing a polyol compound, a surfactant, and water; a curing agent (2) containing a polyisocyanate compound; and a powder component (3) containing cement and coarse aggregate with a particle size of 1 mm or more, The above main component (1) further comprises a vinyl polymer having an alkyl group with 8 or more carbon atoms. A curable composition characterized by the following features. 2. The curable composition according to 1, characterized in that the main component (1) contains a nonionic surfactant. 3. The curable composition according to 1, characterized in that the main component (1) contains castor oil polyol. [Effects of the Invention]
[0009] According to the curable composition of the present invention, a coating with excellent anti-slip properties and finish properties can be formed, while suppressing the penetration of contaminants and maintaining the aesthetic appearance of the coating. [Modes for carrying out the invention]
[0010] The following describes embodiments for carrying out the present invention.
[0011] The curable composition of the present invention comprises a main component (1), a curing agent (2), and a powder component (3).
[0012] Of these, the main component (1) includes a polyol compound, a surfactant, and water.
[0013] The polyol compound in the main component (1) acts as a binder. Examples of polyol compounds include polyester polyols, polyether polyols, acrylic polyols, castor oil polyols, amine-modified polyols, epoxy-modified polyols, silicone-modified polyols, fluorine-modified polyols, polydiene polyols, and cellulose compounds, which can be used individually or in combination of two or more.
[0014] Examples of polyester polyols include condensation polymers of polyhydric alcohols and polyhydric carboxylic acids; ring-opening polymers of cyclic esters (lactones); and reaction products of three components: polyhydric alcohols, polyhydric carboxylic acids, and cyclic esters.
[0015] Examples of polyhydric alcohols include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, triethylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,3-tetramethylenediol, 1,4-tetramethylenediol, 1,6-hexanediol, 1,3-tetramethylenediol, 2-methyl-1,3-trimethylenediol, 1,5-pentamethylenediol, trimethylpentanediol, 2,2,4-trimethyl-1,3-pentanediol, neopentyl glycol, cyclohexanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,6-hexamethylenediol, and 3-methyl-1,5-pentamethylenediol. Examples include methylol, 2,4-diethyl-1,5-pentamethylenediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, metaxylene glycol, paraxylene glycol, bishydroxyethoxybenzene, bishydroxyethyl terephthalate, glycerin, diglycerin, trimethylolpropane, ditrimethylolpropane, trimethylolethane, ester glycols, cyclohexanediols (1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, etc.), bisphenols (bisphenol A, etc.), sugar alcohols (xylitol, sorbitol, etc.), pentaerythritol, dipentaerythritol, 2-methylolpropanediol, ethoxylated trimethylolpropane, etc.
[0016] Examples of polycarboxylic acids include aliphatic dicarboxylic acids such as malonic acid, maleic acid, maleic anhydride, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedionic acid; Alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; Examples include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, phthalic anhydride, terephthalic acid, 2,6-naphthalenedicarboxylic acid, paraphenylenedicarboxylic acid, and trimellitic acid.
[0017] Examples of cyclic esters in ring-opening polymers include propiolactone, β-methyl-δ-valerolactone, and ε-caprolactone. In the reaction product of the three components, the polyhydric alcohol, polyhydric carboxylic acid, and cyclic ester can be those exemplified above.
[0018] Examples of polyether polyols include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polyethylene glycol monoalkyl ether, and polypropylene glycol monoalkyl ether, as well as (alkylene oxide-other alkylene oxide) copolymers containing multiple alkylene oxides as monomer components, such as ethylene oxide-propylene oxide copolymers.
[0019] Examples of acrylic polyols include hydroxyl group-containing alkyl esters obtained by polymerizing and copolymerizing monomers containing hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxy-2-methylpropyl (meth)acrylate, glycerol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol (meth)acrylate, caprolactone-modified (meth)acrylic acid ester, and N-hydroxyethylacrylamide; Monoesters of the above-mentioned polyether polyol and an unsaturated carboxylic acid such as (meth)acrylic acid; Monoesterified or diesterified compounds of acid anhydride group-containing monomers such as maleic anhydride and glycols such as ethylene glycol, propylene glycol, butylene glycol, and 1,6-hexanediol; Hydroxyalkyl vinyl ethers such as hydroxyethyl vinyl ether; allyl alcohol, and the like.
[0020] Examples of the castor oil polyol include a reaction product of castor oil or castor oil fatty acid (including ricinoleic acid and hydrogenated castor oil fatty acid) with the above polyhydric alcohol or the above polyether polyol, and the like.
[0021] Examples of the amine-modified polyol include those obtained by adding an amine compound to the above polyester polyol, the above polyether polyol, or the above acrylic polyol, those obtained by adding an amine compound during the production of the above polyester polyol, the above polyether polyol, or the above acrylic polyol, and the like. In the present invention, it is particularly preferred to use an amine-modified polyether polyol obtained by adding an amine compound to a cyclic ether such as ethylene oxide, propylene oxide, isobutylene oxide, 1,2-epoxybutane, or 2,3-epoxybutane.
[0022] Examples of the amine compound include aliphatic amine compounds, saturated cyclic amine compounds, aromatic amine compounds, and the like. Examples of the aliphatic amine compound include ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, and the like. Examples of the saturated cyclic amine compound include N-aminomethylpiperazine, N-(2-aminoethyl)piperazine, and the like. Examples of the aromatic amine compound include 2,4-toluenediamine, 2,6-toluenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylmethane, p-phenylenediamine, o-phenylenediamine, naphthalenediamine, and the like. These can be used singly or in combination of two or more.
[0023] In the present invention, it is particularly preferable to include castor oil polyol as the polyol compound. Including castor oil polyol can improve the homogeneity of the film surface layer, which is advantageous in terms of improving finish and maintaining aesthetic appearance. The reasons for these effects are not limited to those listed below, but it is presumed that the moderate compatibility of castor oil polyol with the vinyl polymer described later contributes to this. The polyol compound in main component (1) preferably contains 80% by mass or more of castor oil polyol, more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0024] The hydroxyl value of the polyol compound is preferably 50 to 500 mg KOH / g, more preferably 100 to 400 mg KOH / g, and even more preferably 130 to 350 mg KOH / g. A hydroxyl value within this range is favorable in terms of curability, finish, and other properties. Furthermore, the number of hydroxyl functional groups in a single molecule of the polyol compound is preferably 2.0 to 5.0, more preferably 2.5 to 4.0. A number of functional groups within this range is favorable in terms of finish, and other properties. In this invention, "α to β" is generally synonymous with "α or greater and β or less".
[0025] Examples of surfactants in the main component (1) include nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants. Among these, in the present invention, an embodiment containing a nonionic surfactant is preferred in terms of improving the finish.
[0026] Nonionic surfactants are not particularly limited in type, but examples include polyoxyethylene alkylaryl ethers such as polyoxyethylene nonylphenyl ether and polyoxyethylene octylphenyl ether; polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, and polyoxyethylene oleyl ether; and others such as polyoxyethylene sorbitan fatty acid esters, polyoxyethylene fatty acid esters, and ethylene oxide-propylene oxide copolymers. These can be used individually or in combination of two or more.
[0027] Nonionic surfactants with an HLB of 9 or higher are preferred, those with an HLB of 10 to 20 are more preferred, and those with an HLB of 12 to 18 are even more preferred. The use of nonionic surfactants having such an HLB is even more preferable in terms of improving finish properties. HLB is an abbreviation for hydrophilic-lipophilic balance, and is a numerical representation of the ratio of hydrophilicity to lipophilicity intensity of an amphiphilic substance, and is specifically calculated using Griffin's formula.
[0028] The ratio of nonionic surfactant is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.3 to 3 parts by mass, per 100 parts by mass of the polyol compound, based on solid content. With such a ratio, sufficient effects can be obtained in terms of finish and other properties.
[0029] The water in the main component (1) contributes to the curing reaction when the main component (1), curing agent (2), and powder component (3) are mixed. The ratio of water is preferably 20 to 200 parts by mass, more preferably 30 to 150 parts by mass, per 100 parts by mass of the solid content of the polyol compound. This mixing ratio allows for sufficient effects in terms of curability, strength, etc.
[0030] In the present invention, the main component (1) further contains a vinyl polymer having an alkyl group with 8 or more carbon atoms (hereinafter also simply referred to as "vinyl polymer"). In the present invention, by containing such a vinyl polymer having a specific alkyl group in the main component (1), the occurrence of gloss unevenness, color unevenness, and fine voids is suppressed during film formation, improving the finish and providing effects such as stain prevention and aesthetic maintenance. The reasons for achieving these effects are not limited to the following, but in the composition of the present invention, when the main component (1), hardener (2), and powder component (3) are mixed, the urethane reaction between the polyol compound and the polyisocyanate compound, the urea reaction between the polyisocyanate compound and water, and the hydration reaction between cement and water proceed simultaneously to form a hardened film. In this invention, it is presumed that during the film formation process, the vinyl polymer controls the orientation of each component based on the hydrophobicity of its alkyl group so that a homogeneous resin layer is formed on the outermost surface of the film through a urethane reaction between the polyol compound and the polyisocyanate compound, and / or a urea reaction between the polyisocyanate compound and water.
[0031] Vinyl polymers are polymers obtained by polymerization of a group of vinyl-based unsaturated compounds that exhibit radical polymerization properties. Examples of vinyl-based unsaturated compounds that constitute vinyl polymers include (meth)acrylate alkyl esters, alkyl vinyl ethers, and other vinyl-based unsaturated compounds. These can be used individually or in combination of two or more. In this invention, alkyl acrylates and alkyl methacrylates are collectively referred to as (meth)acrylate alkyl esters.
[0032] The vinyl polymer in the present invention has an alkyl group having 8 or more carbon atoms, preferably an alkyl group having 8 to 22 carbon atoms. Examples of vinyl-based unsaturated compounds that constitute such a vinyl polymer include alkyl (meth)acrylates having an alkyl group having 8 or more carbon atoms (preferably 8 to 22 carbon atoms), alkyl vinyl ethers having an alkyl group having 8 or more carbon atoms (preferably 8 to 22 carbon atoms), and the like.
[0033] Examples of alkyl (meth)acrylates having an alkyl group with 8 or more carbon atoms include n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, dodecyl (meth)acrylate, isododecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, hexadecyl (meth)acrylate, isohexadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, behenyl (meth)acrylate, etc. These can be used individually or in combination of two or more.
[0034] Examples of alkyl vinyl ethers having an alkyl group with 8 or more carbon atoms include n-octyl vinyl ether, 2-ethylhexyl vinyl ether, nonyl vinyl ether, isononyl vinyl ether, decyl vinyl ether, isodecyl vinyl ether, dodecyl vinyl ether, tetradecyl vinyl ether, hexadecyl vinyl ether, and octadecyl vinyl ether. These can be used individually or in combination of two or more.
[0035] In the present invention, it is desirable that, of the group of vinyl-based unsaturated compounds constituting the vinyl polymer, preferably 60% by mass or more (more preferably 70-100% by mass, and even more preferably 80-98% by mass) are alkyl (meth)acrylates having an alkyl group having 8 or more carbon atoms, and / or alkyl vinyl ethers having an alkyl group having 8 or more carbon atoms. Furthermore, in the present invention, it is preferable that the group of vinyl-based unsaturated compounds constituting the vinyl polymer includes at least alkyl (meth)acrylates having an alkyl group having 10-20 carbon atoms, and / or alkyl vinyl ethers having an alkyl group having 10-20 carbon atoms.
[0036] Other vinyl unsaturated compounds can also be used as the vinyl unsaturated compounds constituting the vinyl polymer. Examples of other vinyl unsaturated compounds include alkyl (meth)acrylates having alkyl groups with fewer than 8 carbon atoms, alkyl vinyl ethers having alkyl groups with fewer than 8 carbon atoms, vinyl unsaturated compounds containing carboxyl groups, vinyl unsaturated compounds containing carbonyl groups, vinyl unsaturated compounds containing amino groups, vinyl unsaturated compounds containing hydroxyl groups, vinyl unsaturated compounds containing nitrile groups, vinyl unsaturated compounds containing amide groups, vinyl unsaturated compounds containing sulfonic acid groups, vinyl unsaturated compounds containing polyoxyalkylene chains, vinyl unsaturated compounds containing nitrogen rings, vinyl unsaturated compounds containing oxygen rings, and aromatic vinyl unsaturated compounds. These can be used individually or in combination of two or more. The proportion of other vinyl unsaturated compounds is preferably 40% by mass or less, more preferably 0 to 30% by mass, and even more preferably 2 to 20% by mass, of the group of vinyl unsaturated compounds constituting the vinyl polymer.
[0037] The weight-average molecular weight of the vinyl polymer is preferably 2,000 to 400,000, more preferably 3,000 to 200,000.
[0038] The ratio of vinyl polymer is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, and even more preferably 2 to 15 parts by mass, per 100 parts by mass of polyol compound, based on solid content. With such a ratio, sufficient effects can be obtained in terms of finish and aesthetic maintenance.
[0039] The main component (1) can be produced by uniformly mixing the above-mentioned polyol compound, surfactant, water, and a polymer having an alkyl group with 8 or more carbon atoms using a conventional method. In this process, the main component (1) may also be mixed with other components as needed, such as plasticizers, basic compounds, defoamers, reaction modifiers, water-reducing agents, fibers, preservatives, anti-algal agents, antifungal agents, and silane coupling agents.
[0040] Among these, plasticizers that can be used include, for example, phthalate compounds, adipic acid compounds, sebatic acid compounds, phosphoric acid compounds, and alkyl sulfonic acid ester compounds. Specifically, examples of phthalate compounds include di(n-butyl) phthalate, bis(2-ethylhexyl) phthalate, diisononyl phthalate, and butyl benzyl phthalate. Examples of adipic acid compounds include di(n-butyl) adipate and bis(2-ethylhexyl) adipate; examples of sebatic acid compounds include dibutyl sebatate; examples of fumarate compounds include dibutyl fumarate; examples of phosphate compounds include tricresyl phosphate and cresyl diphenyl phosphate; examples of alkyl sulfonic acid ester compounds include phenyl decanesulfonate, phenyl undecanesulfonate, phenyl dodecanesulfonate, phenyl tridecanesulfonate, phenyl tetradecanesulfonate, phenyl pentadecanesulfonate, cresyl pentadecanesulfonate, phenyl hexadecanesulfonate, phenyl heptadecanesulfonate, phenyl octadecanesulfonate, phenyl nonadecanesulfonate, and phenyl eicosandecylsulfonate. One or more of these can be used as plasticizers. The mixing ratio of the plasticizer is preferably 20 to 200 parts by mass, more preferably 30 to 150 parts by mass, per 100 parts by mass of the solid content of the polyol compound.
[0041] Examples of basic compounds that can be used include ammonia, alkylamines, alkanolamines, alkali metal salts, and alkali metal silicates. Examples of alkylamines include monoethylamine, diethylamine, triethylamine, isopropylamine, and diisopropylamine. Examples of alkanolamines include aminoethanol, aminopropanol, N,N-dimethylethanolamine, N,N-diethylethanolamine, N-methylethanolamine, and N-methyldiethanolamine. Examples of alkali metal salts that can be used include alkali metal hydroxides, carbonates, and bicarbonates. Specifically, examples include lithium hydroxide, sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, iron hydroxide, potassium carbonate, potassium bicarbonate, sodium carbonate, and sodium bicarbonate. These can be used individually or in combination of two or more. The mixing ratio of the basic compounds is preferably 0.001 to 2 parts by mass, more preferably 0.01 to 1 part by mass, per 100 parts by mass of the solid content of the polyol compound.
[0042] The curing agent (2) of the present invention contains a polyisocyanate compound. The polyisocyanate compound is a compound having two or more isocyanate groups in one molecule, and specifically includes, for example, 4,4-diphenylmethane diisocyanate (pure-MDI), polymeric MDI, xylylene diisocyanate (XDI), tolylene diisocyanate, hexamethylene diisocyanate (HMDI), isophorone diisocyanate (IPDI), hydrogenated XDI, hydrogenated MDI, etc., or derivatives of these obtained by allophanation, biuretation, dimerization (uretidioneation), trimerization (isocyanurateation), adductation, carbodiimideation, etc. Isocyanate-terminated prepolymers obtained by the reaction of isocyanate and polyol can also be used. One or more of these can be used as the polyisocyanate compound.
[0043] The curing agent (2) preferably contains 50% by mass or more of a polyisocyanate compound, more preferably 80% by mass or more, and even more preferably 90% by mass or more. An embodiment in which the curing agent (2) consists of a polyisocyanate compound is also preferred.
[0044] The polyisocyanate compound of the curing agent (2) should be mixed in an amount preferably 50 to 800 parts by mass, more preferably 100 to 500 parts by mass, relative to 100 parts by mass of the solid content of the polyol compound of the main component (1).
[0045] The powder component (3) contains cement and coarse aggregate with a particle size of 1 mm or more. Examples of cement include Portland cement such as ordinary Portland cement, rapid-hardening Portland cement, ultra-rapid-hardening Portland cement, moderate-heat Portland cement, sulfate-resistant Portland cement, and white Portland cement, as well as alumina cement, ultrafast-setting cement, expansive cement, acidic phosphate cement, silica cement, blast furnace cement, fly ash cement, and Kiens cement. These can be used individually or in mixtures of two or more. Among these, Portland cement is preferred.
[0046] The cement of powder component (3) should be mixed in an amount preferably between 100 and 1000 parts by mass, more preferably between 200 and 800 parts by mass, relative to 100 parts by mass of the solid content of the polyol compound of the main component (1).
[0047] The powder component (3) contains, in addition to cement, coarse aggregate with a particle size of 1 mm or more. In this invention, by mixing in such coarse aggregate, fine irregularities can be formed on the surface of the coating, thereby providing anti-slip properties. Moreover, in this invention, even when such coarse aggregate is mixed in, the generation of fine voids in the formed coating is suppressed, and excellent effects can be achieved in terms of finish and aesthetic maintenance.
[0048] The particle size of the coarse aggregate is 1 mm or larger, preferably 1 to 10 mm. Examples of coarse aggregate include crushed natural stone, ceramic powder, silica sand, gravel, ceramic powder, rubber granules, metal granules, etc., or those with a colored coating on their surface. These can be used individually or in combination of two or more types. The mixing ratio of the coarse aggregate is preferably 100 to 2000 parts by mass, more preferably 200 to 1000 parts by mass, per 100 parts by mass of the solid content of the polyol compound of the main component (1).
[0049] The coarse aggregate preferably contains 30% by mass or more (more preferably 50-100% by mass, and even more preferably 60-95% by mass) of particles with a particle size of 1.4 mm or larger. By mixing in such coarse aggregate, it is possible to further suppress the generation of fine voids in the formed coating while providing anti-slip properties, thereby improving the finish and maintaining aesthetic appeal.
[0050] The powder component (3) may further contain fine aggregate. Including such fine aggregate can improve the strength and thickness of the coating. Examples of fine aggregate include crushed natural stone, ceramic powder, silica sand, ceramic powder, rubber granules, metal granules, or materials with colored coatings on their surfaces. The particle size of the fine aggregate is preferably less than 1000 μm, more preferably 53 to 1000 μm, and even more preferably 75 to 1000 μm. The fine aggregate should be mixed in an amount of preferably 3000 parts by mass or less, more preferably 200 to 3000 parts by mass, and even more preferably 500 to 2500 parts by mass, per 100 parts by mass of the solid content of the polyol compound of the main component (1). The particle size of the coarse aggregate and fine aggregate is measured by sieving using a metal mesh sieve as specified in JIS Z8801-1:2019. Regarding the particle size of fine aggregate and coarse aggregate, "α or greater" and "α~" are synonymous, meaning particles that cannot pass through a sieve with a mesh size of α, "less than β" and "~β" are synonymous, meaning particles that can pass through a sieve with a mesh size of β, and α~β means particles that cannot pass through a sieve with a mesh size of α, but can pass through a sieve with a mesh size of β.
[0051] The fine aggregate preferably contains 50% by mass or more (more preferably 60% by mass to 100% by mass, and even more preferably 65% by mass to 99% by mass) of particles with a diameter of 425 to 1000 μm. By mixing in such fine aggregate, the generation of fine voids in the formed film can be further suppressed, thereby improving the finish and maintaining aesthetic appeal. It is also preferable in terms of improving the strength and thickness of the film.
[0052] In the present invention, the ratio of fine aggregate with a particle size of 425 to 1000 mm to the total amount of coarse aggregate is preferably 40 to 97% by mass, more preferably 50 to 95% by mass, and even more preferably 55 to 93% by mass. Furthermore, the ratio of coarse aggregate with a particle size of 1.4 mm or larger to the total amount of coarse aggregate and fine aggregate is preferably 3 to 45% by mass, more preferably 5 to 35% by mass, and even more preferably 7 to 30% by mass. In this invention, by mixing coarse aggregate and fine aggregate in this manner, it is possible to further suppress the generation of fine voids while providing anti-slip properties to the formed coating, thereby improving effects such as finish quality and aesthetic appeal.
[0053] The powder component (3) may further contain a carbon dioxide absorbent. Examples of carbon dioxide absorbents include calcium oxide, magnesium oxide, barium oxide, sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, barium hydroxide, magnesium hydroxide, calcium silicate, barium silicate, and sodium silicate. The carbon dioxide absorbent should be mixed in an amount of preferably 200 parts by mass or less, more preferably 5 to 200 parts by mass, and even more preferably 10 to 150 parts by mass, relative to 100 parts by mass of the solid content of the polyol compound of the main component (1).
[0054] The curable composition of the present invention may contain coloring pigments. Examples of coloring pigments include titanium dioxide, zinc oxide, carbon black, graphite, black iron oxide, iron-manganese composite oxide, iron-copper-manganese composite oxide, iron-chromium composite oxide, iron-chromium-cobalt composite oxide, copper-chromium composite oxide, copper-manganese-chromium composite oxide, copper-magnesium composite oxide, bismuth-manganese composite oxide, red iron oxide, molybdate orange, permanent red, permanent carmine, anthraquinone red, perylene red, quinacridone red, yellow iron oxide, titanium yellow, first yellow, benzoimidazolone yellow, chromium green, chromium oxide green, cobalt green, phthalocyanine green, ultramarine, Prussian blue, cobalt blue, phthalocyanine blue, quinacridone violet, and dioxazine violet. These can be used individually or in combination of two or more. By including such coloring pigments, it is possible to prepare the curable composition to a desired color. The average particle size of the coloring pigment is preferably 2 μm or less, more preferably 0.01 to 1 μm. The average particle size of the coloring pigment is a value measured by a laser diffraction particle size distribution analyzer.
[0055] Such coloring pigments can be mixed with, for example, the main component (1), the curing agent (2), or the powder component (3), or they can be prepared as components separate from the main component (1), the curing agent (2), and the powder component (3). The coloring pigment should be mixed in a range of preferably 4 to 80 parts by mass, more preferably 6 to 60 parts by mass, per 100 parts by mass of the solid content of the polyol compound in the main component (1).
[0056] In the present invention, it is desirable to prepare a coloring solution (4) containing a coloring pigment and alkyl sulfonate phenyl ester as a component separate from the main agent (1), curing agent (2), and powder component (3). In the present invention, by using such a coloring solution (4), when the main agent (1), curing agent (2), powder component (3), and coloring solution (4) are mixed and applied as paint, superior performance in terms of color uniformity and finish can be achieved. The reasons for achieving such effects are not limited to the following, but it is presumed that the alkyl sulfonate phenyl ester in the coloring solution (4) contributes to the dispersion stability of the coloring pigment, and that the alkyl sulfonate phenyl ester is easily compatible with the main agent (1), etc.
[0057] As alkylsulfonic acid phenyl esters, for example, compounds represented by the following general formula (I) can be used.
[0058] [ka]
[0059] Examples of alkyl sulfonate phenyl esters represented by such compounds include decanesulfonate phenyl ester, undecanesulfonate phenyl ester, dodecanesulfonate phenyl ester, tridecanesulfonate phenyl ester, tetradecanesulfonate phenyl ester, pentadecanesulfonate phenyl ester, hexadecanesulfonate phenyl ester, heptadecanesulfonate phenyl ester, octadecanesulfonate phenyl ester, nonadecanesulfonate phenyl ester, and eicosandecylsulfonate phenyl ester. These can be used individually or in combination of two or more.
[0060] The ratio of coloring pigment in the coloring solution (4) is preferably 30 to 80% by mass, more preferably 40 to 70% by mass. The ratio of alkyl sulfonate phenyl ester in the coloring solution (4) is preferably 20 to 70% by mass, more preferably 30 to 60% by mass.
[0061] Furthermore, the coloring pigment of the coloring solution (4) should be mixed in a range of preferably 4 to 80 parts by mass, more preferably 6 to 60 parts by mass, per 100 parts by mass of the solid content of the polyol compound of the main component (1). The alkyl sulfonate phenyl ester of the coloring solution (4) should be mixed in a range of preferably 2 to 60 parts by mass, more preferably 3 to 50 parts by mass, per 100 parts by mass of the solid content of the polyol compound of the main component (1).
[0062] The coloring solution (4) may also contain additives as needed, such as defoaming agents, reaction modifiers, water-reducing agents, extender pigments, fibers, preservatives, algaecides, and fungicides.
[0063] The curable composition of the present invention is distributed with the main component (1), hardener (2), and powder component (3) stored in separate packages, and these can be mixed at the time of use (immediately before painting). When using the above-mentioned coloring liquid (4), the main component (1), hardener (2), powder component (3), and coloring liquid (4) are stored in separate packages during distribution, and these can be mixed at the time of use. Two or more coloring liquids (4) with different colors can also be prepared. In addition, a curing accelerator (5), etc., can be prepared separately and mixed at the time of use.
[0064] The curable composition of the present invention can form a coating by mixing the above components at the time of use and applying the mixture to a substrate. In addition to its finish, the composition of the present invention exhibits excellent physical properties such as chemical resistance and strength, making it particularly preferable as a material to be applied to floor surfaces such as concrete.
[0065] During painting, various methods can be employed, such as trowel application, pouring, roller application, and spraying. The thickness after curing is preferably 1 to 12 mm, more preferably 2 to 10 mm. It is also possible to apply the coating in multiple coats to achieve this predetermined thickness. Painting and subsequent drying should preferably be carried out at room temperature (0-40°C). [Examples]
[0066] The following examples illustrate the features of the present invention. However, the present invention is not limited to the examples provided herein.
[0067] (Main ingredient) For the main component, a mixture of each ingredient was prepared according to the formulation shown in Table 1. The raw materials used for the main component are as follows:
[0068] • Resin 1: Castor oil polyol (hydroxyl value 160 KOH mg / g, solids content 100% by mass) • Resin 2: Castor oil polyol (hydroxyl value 320 KOH mg / g, solids content 100% by mass) • Resin 3: Polyether polyol (hydroxyl value 450 KOH mg / g, solids content 100% by mass) • Surfactant 1: Nonionic surfactant (polyoxyethylene alkyl ether, HLB 9.7, solids content 100% by mass) • Surfactant 2: Nonionic surfactant (polyoxyethylene alkyl ether, HLB 13.4, solids content 100% by mass) • Surfactant 3: Nonionic surfactant (polyoxyethylene alkyl ether, HLB 15.0, solids content 100% by mass) • Vinyl polymer 1:2-ethylhexyl acrylate-dodecyl vinyl ether (mass ratio 50:50) copolymer solution (weight-average molecular weight 180,000, solids content 70% by mass) • Vinyl polymer 2:2-ethylhexyl acrylate-octadecyl methacrylate (mass ratio 50:50) copolymer solution (weight-average molecular weight 60,000, solids content 70% by mass) • Vinyl polymer 3: Dodecyl vinyl ether-tetradecyl vinyl ether-hexadecyl vinyl ether (mass ratio 25:55:20) copolymer solution (weight-average molecular weight 30,000, solids content 70% by mass) • Plasticizer 1: Phenyl alkylsulfonate (compound represented by the general formula (I) above)
[0069] [Table 1]
[0070] (Hardening agent) As the curing agent 1, a polyisocyanate compound (polymeric MDI, NCO content 31% by mass) was prepared.
[0071] (Powdered components) The following powder components were prepared:
[0072] • Powder component 1: Cement (Portland cement), Fine aggregate 1 (white silica sand, particle size 212-1000 μm, 90% by mass of particle size 425-1000 μm), Coarse aggregate 1 (crushed ceramic material, particle size 1-3.35 mm, proportion of particles 1.4 mm or larger 82% by mass), A mixture with a carbon dioxide absorbent (calcium hydroxide) (mass ratio 10:76:10:4). The ratio of coarse aggregate with a particle size of 1.4 mm or larger to the total amount of coarse aggregate and fine aggregate is 10% by mass. The ratio of fine aggregate with a particle size of 425-1000 mm to the total amount of coarse aggregate is 80% by mass.
[0073] • Powder component 2: Cement (Portland cement), Fine aggregate 2 (white silica sand, particle size 180-1000 μm, 88% by mass of particle size 425-1000 μm), Coarse aggregate 1 (crushed ceramic material, particle size 1-3.35 mm, proportion of particles 1.4 mm or larger 82% by mass), Coarse aggregate 2 (silica sand, particle size 1-2.8 mm, proportion of particles 1.4 mm or larger 84% by mass), A mixture with a carbon dioxide absorbent (calcium hydroxide) (mass ratio 10:62:10:15:3). The ratio of coarse aggregate with a particle size of 1.4 mm or larger to the total amount of coarse aggregate and fine aggregate is 24% by mass. The ratio of fine aggregate with a particle size of 425-1000 mm to the total amount of coarse aggregate is 63% by mass.
[0074] • Powder component 3: Cement (Portland cement), Fine aggregate 1 (white silica sand, particle size 212-1000 μm, 90% by mass of particle size 425-1000 μm), Coarse aggregate 3 (crushed ceramic material, particle size 1-2 mm, with 48% by mass of particles 1.4 mm or larger), A mixture with a carbon dioxide absorbent (calcium hydroxide) (mass ratio 10:79:7:4). The ratio of coarse aggregate with a particle size of 1.4 mm or larger to the total amount of coarse aggregate and fine aggregate is 4% by mass. The ratio of fine aggregate with a particle size of 425-1000 mm to the total amount of coarse aggregate is 83% by mass.
[0075] (Colored liquid) The following coloring solutions were prepared: • Coloring solution 1: A mixture of coloring pigment 1 (titanium dioxide), coloring pigment 2 (chromium oxide green), coloring pigment 4 (carbon black), and alkyl sulfonate phenyl ester (a compound represented by the general formula (I) mentioned above) (mass ratio 2:42:1:55). • Coloring solution 2: A mixture of coloring pigment 1 (titanium dioxide), coloring pigment 2 (chromium oxide green), coloring pigment 4 (carbon black), and diisononyl phthalate (mass ratio 2:42:1:55).
[0076] (Curable composition) A curable composition was prepared by mixing the main component, curing agent, powder component, and coloring liquid in a mass ratio of 10:10:100:1. The combinations of main component, curing agent, powder component, and coloring liquid used in each curable composition are shown in Table 2.
[0077] (test) Each of the resulting curable compositions was tested using the following method. The test results are shown in Table 2.
[0078] (Test 1; Anti-slip properties) Each curable composition obtained by the above method was applied to a slate board with a trowel to a predetermined thickness (4 mm or 6 mm) after curing, and then dried and cured for 72 hours. The slip resistance of the coating was then checked. The evaluation was performed on a three-tiered scale (Excellent: A > B > C: Poor), with "A" indicating that surface irregularities were formed by the aggregate and slip resistance was observed, and "C" indicating that no slip resistance was observed. Painting and curing were carried out under standard conditions (temperature 23°C, relative humidity 50%).
[0079] (Test 2; Finish) For each curable composition obtained by the above method, a test specimen was prepared by troweling the composition onto the left half of a slate board so that the cured thickness was a predetermined thickness (4 mm or 6 mm), 5 minutes later, then troweling the remaining right half, smoothing the entire surface with a trowel, and drying and curing for 72 hours. The finish quality of the coating on the test specimen was visually inspected. The evaluation was performed on a three-tiered scale (Excellent: A > B > C: Poor), with "A" indicating excellent finish quality with generally inconspicuous fine voids, color unevenness, and gloss unevenness, and "C" indicating noticeable fine voids, color unevenness, or gloss unevenness. Painting and curing were carried out under standard conditions (temperature 23°C, relative humidity 50%).
[0080] (Test 3; Aesthetic Retention) In the test specimens prepared in Test 2 above, a contaminant (soy sauce) was dropped onto the surface of the coating, left for 48 hours, and then wiped off. The condition of the coating was then visually inspected. The evaluation was performed on a three-level scale (Excellent: A > B > C: Poor), with "A" indicating no contamination and "C" indicating contamination.
[0081] [Table 2]
Claims
1. A curable composition comprising a main component (1) containing a polyol compound, a surfactant, and water; a curing agent (2) containing a polyisocyanate compound; and a powder component (3) containing cement and coarse aggregate with a particle size of 1 mm or more, The main component (1) further comprises a vinyl polymer having an alkyl group with 8 or more carbon atoms. A curable composition characterized by the following features.
2. The curable composition according to claim 1, characterized in that the main component (1) contains a nonionic surfactant.
3. The curable composition according to claim 1, characterized in that the main component (1) contains a castor oil polyol.
Citation Information
Patent Citations
Cement composition and polyol composition for formation of coating floor
JP2020015647A